2005
DOI: 10.1177/0269881105049037
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a combined genetic effect of the 5-HT1A receptor and serotonin transporter genes in the clinical outcome of major depressive patients treated with citalopram

Abstract: In the context of a long-term follow-up study, we analysed the possible implication of the 5-HT(1A) receptor gene (HTR1A) -1018C/G polymorphism in the clinical outcome of major depressive patients treated with citalopram. We had previously reported an association between variation on the SERT gene (SLC6A4) and clinical remission after citalopram treatment. In the present 12-week follow-up study, the combined effect of HTR1A and SLC6A4 genes in clinical outcome and response to citalopram was also evaluated. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(50 citation statements)
references
References 46 publications
5
45
0
Order By: Relevance
“…8 The À1019G allele or the homozygous À1019GG genotype has been associated with depression, suicide, bipolar disorder, panic disorder with agoraphobia, neuroticism and decreased antidepressant response. [8][9][10][11][12][13][14][15] We tested the hypothesis that the HTR1A À1019G allele increases depression risk in a Utah population. Observed frequencies of À1019G allele (350/688) and À1019GG genotype (89/344) were 1.10-and 1.34-fold higher among unrelated individuals affected with MDD compared to unaffected individuals (312/672 and 65/336; one-tailed Fisher's exact test P = 0.05 and 0.02, respectively).…”
Section: Serotonin Receptor 1a-conditional Genetic Analysismentioning
confidence: 99%
“…8 The À1019G allele or the homozygous À1019GG genotype has been associated with depression, suicide, bipolar disorder, panic disorder with agoraphobia, neuroticism and decreased antidepressant response. [8][9][10][11][12][13][14][15] We tested the hypothesis that the HTR1A À1019G allele increases depression risk in a Utah population. Observed frequencies of À1019G allele (350/688) and À1019GG genotype (89/344) were 1.10-and 1.34-fold higher among unrelated individuals affected with MDD compared to unaffected individuals (312/672 and 65/336; one-tailed Fisher's exact test P = 0.05 and 0.02, respectively).…”
Section: Serotonin Receptor 1a-conditional Genetic Analysismentioning
confidence: 99%
“…The short allele is generally associated with reduced transporter activity and lower SLC6A4 expression 19 -precisely the functional effect of the SSRIs used to treat depression -although a recent study investigating allelic expression in the serotonin transporter gene found no correlation between expression levels and the promoter polymorphism. 20 Other genes that have been putatively associated with MDD include those encoding tryptophan hydroxylase, 21 brain-derived neurotrophic factor, 22,23 catechol-O-methyl transferase, 24 phospholipase A2, 25 the glucocorticoid receptor 26 and the serotonin receptor 1A, 27 although these findings still await convincing replication in other samples (see Levinson 28 a recent review).…”
mentioning
confidence: 99%
“…4,5 In several studies, these variants were associated with responses including the antidepressant response in MDD. [24][25][26][27][28][29] Recently, Kato and Serretti 30 reported a meta-analysis between rs6295 and antidepressant efficacy in MDD. The authors showed that the pooled OR derived from six studies comprising 893 patients was not significant.…”
Section: Discussionmentioning
confidence: 99%